Malowanie trawy Rzecz (jeszcze) mniejsza o peryferyjnej humanistyce - Kubiak, Adam (Śląskie Studia Polonistyczne, 2017)
The text attempts to resolve the narrative impasse perpetuating in analyses and reconstructions of the local humanities position in the field of local and supra-local competition. The basic proposal that can lead to the most sensible and credible debate in this matter is the preliminary establishment of the local representatives of (broadly understood) humanities beyond the standard narratives (progress, backwardness, worldliness etc.) and fantasies abundantly present in this discourse. This suggestion may be strongly uncomfortable for the actors acting in this field, but it seems that without undertaking such a confrontation these analyzes and debates will remain sterile, regardless of how instrumentally effective they may be in clashes between individual fractions within the local field of humanities.